Clinical characteristics of patients with hereditary transthyretin amyloid cardiomyopathy (ATTR-CM) in Sarawak - Hwei Sung, Ling; Chen, L. S.; Oon, Y.Y.; Chung, B.K.; Thien, L.K.; Chow, H.B.; Pang, I. X.; Ling, H, S,; Chandan, D.B.; Tan, C. T.; Koh, K.T.; Asri, Said; et al. (Elsevier Inc., 2021)
Abstract We describe the clinical characteristic of patients diagnosed with hereditay transthyretin amyloid cardiomyopathy (ATTRv-CM) in the multi-ethic Malaysian population in Sarawak. From April 2019 to September 2021, we diagnosed 6 patients with ATTRv-CM of which 5 (83%) were male, median age of disease onset was 53.5 years, median duration from symptoms onset to diagnosis was 34 months. 2 patients (33%) were in New York Heart Association functional class I, 1 in NYHA class II (17%), 3 (50%) in class III or IV at time of diagnosis. The median NT-proBNP level was 806pg/ml (range 227-10900pg/ml) and the median Hs-Troponin was 45pg/ml (range 37-211pg/ml). The genetic mutations identified were p. Glu74Lys in 2 Malay siblings (33%), p. Ala117Ser in 2 unrelated Chinese patients (33%) and p. Val142lle in 2 Bidayuh siblings (33%). Patients with p. Glu74Lys mutation were young, and had predominant neurological manifestation and subtle cardiac features. p. Ala117Ser mutation was characterised by initial protracted neurological presentation followed by heart failure, while p. Val142lle mutation was characterised by predominant cardiac manifestation. The common electrocardiography findings were mismatch between QRS voltage and left ventricular (LV) wall thickness (67%), premature atrial contraction (50%) and first-degree atrioventricular block (50%). Echocardiography findings included symmetrical LV hypertrophy (100%) with median inter-ventricular septum’s thickness 15.5 mm (range 12-20mm), apical sparing global longitudinal strain pattern (100%), absence of interatrial drop-off (100%) and granular sparkling of myocardium (83%). The median left ventricular ejection fraction was 51% (range 26-72%) and median global longitudinal strain was -11.6% (range -9.4 to -14.6%). 4 patients underwent cardiac MRI. The median native T1 and extracellular volume fraction were increased at 1151 msec (range 1023-1371msec) and 57% (range 52-69%) respectively. Abnormal myocardial nulling was observed in 3 patients, another had diffuse subendocardial late gadolinium enhancement pattern involving the left ventricle and left atrium. Overall survival after 1 month and 6 months of diagnosis was 67% and 50% respectively. 4 patients were started on oral Tafamidis. In conclusion, the clinical characteristics of patients with hereditary ATTR-CM in Sarawak are heterogenous. Diagnosis is often delayed resulting in poor outcome.